2016
DOI: 10.1016/j.bbadis.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for synergistic action of transthyretin and IGF-I over the IGF-I receptor

Abstract: Transthyretin (TTR) has a neuroprotective role in the central nervous system (CNS) in Alzheimer's disease (AD) and cerebral ischemia. Increased levels of TTR and activated insulin-like growth factor I receptor (IGF-IR) are associated with reduced neurodegeneration in an AD mouse model. In the present study, we found that TTR and IGF-I have a synergistic effect on activation of one of the IGF-IR signaling pathways. Hippocampus of TTR null mice present decreased levels of phosphorylated IGF-IR and Akt when compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…IGF-1 supplementation did not modulate hippocampal expression of IGF1R or IGF1 or its downstream signaling elements at P5 and P9, indicating that physiological IGF-1 signaling in the brain was maintained. On the other hand, it cannot be excluded that the transient downregulation of TTR mRNA, encoding protein transthyretin, might negatively affect hippocampal IGF1R expression ( Vieira et al, 2015 ), as it is known to act synergistically with IGF-1 on IGF1R activation ( Vieira et al, 2016 ). Alternatively, the transient alterations in the expression of IGF-1 and related genes might arise before P5, as it was recently shown for IGF-1 expression in the choroid plexus of preterm rabbit pups treated with IGF-1/IGFBP3 complex ( Gram et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 supplementation did not modulate hippocampal expression of IGF1R or IGF1 or its downstream signaling elements at P5 and P9, indicating that physiological IGF-1 signaling in the brain was maintained. On the other hand, it cannot be excluded that the transient downregulation of TTR mRNA, encoding protein transthyretin, might negatively affect hippocampal IGF1R expression ( Vieira et al, 2015 ), as it is known to act synergistically with IGF-1 on IGF1R activation ( Vieira et al, 2016 ). Alternatively, the transient alterations in the expression of IGF-1 and related genes might arise before P5, as it was recently shown for IGF-1 expression in the choroid plexus of preterm rabbit pups treated with IGF-1/IGFBP3 complex ( Gram et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that TTR may act via the IGF-IR signalling pathway synergistically with IGFI [ 44 ]. However, our results revealed that supplementation with IGF-I did not affect metabolism of neither the FM-treated nor the CM-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…TTR is able to increase IGF-I receptor levels, demonstrated in null and wild-type mice and in vitro-cultured cells [115]. Subsequently, it was found that TTR has a synergistic action with IGF-I over the IGF-I receptor, activating the Akt pathway, which is a specific IGF-I receptor signaling pathway [116].…”
Section: Transthyretin As a Gene Regulatormentioning
confidence: 99%